Thiolated poly(aspartic acid)-functionalized two-dimensional MoS2, chitosan and bismuth film as a sensor platform for cadmium ion detection. Issue 62 (14th October 2020) - Cao, Qiang; Xiao, Yushi; Huang, Rong; Liu, Na; Chi, Hai; Lin, Cheng-Te; Huang, Chi-Hsien; Han, Gang; Wu, Lidong
Abstract : In this work, a sensitive electrochemical platform for determination of cadmium ions (Cd 2+ ) is obtained using thiolated poly(aspartic acid) (TPA)-functionalized MoS2 as a sensor platform by differential pulse anodic stripping voltammetry (DPASV). Abstract : In this work, a sensitive electrochemical platform for determination of cadmium ions (Cd 2+ ) is obtained using thiolated poly(aspartic acid) (TPA)-functionalized MoS2 as a sensor platform by differential pulse anodic stripping voltammetry (DPASV). The performance of the TPA–MoS2 -modified sensor is systemically studied. It demonstrates that the TPA–MoS2 nanocomposite modified sensor exhibits superior analytical performance for Cd 2+ over a linear range from 0.5 μg L −1 to 50 μg L −1, with a detection limit of 0.17 μg L −1 . Chitosan is able to form a continuous coating film on the surface of the GC electrode. The good sensing performance of the TPA–MoS2 -modified sensor may be attributed to the following factors: the large surface area of MoS2 (603 m 2 g −1 ), and the abundant thiol groups of TPA. Thus, the TPA–MoS2 -modified sensor proves to be a reliable and environmentally friendly tool for the effective monitoring of Cd 2+ existing in aquacultural environments.